Integrating the Protection Motivation Theory Scale Among Older Adults : Insights for Fall Prevention Behaviour - Mei Fong, Ong; Kim Lam, Soh; Rosalia, Saimon; Ing Khieng, Tiong; Hasni Idayu, Saidi; Manfred, Mortell (Universiti Malaysia Sabah (UMS), 2025)
This commentary examines the application of the Protection Motivation Theory (PMT) scale to evaluate older adults' threat and coping appraisals, fear, and protective behaviours in reducing fall risks. The findings highlighted the impact of fear, threat and coping appraisals on older adults' intentions to adopt protection motivation to reduce fall risk. Mediating effects are found in coping appraisal for protective behaviour, fear for perceived cost, and threat appraisal for protection motivation. This study has also emphasised the implications of adopting the PMT scale among older adults in Sarawak, Malaysia.